Oak habitat recovery on California's largest islands: Scenarios for the role of corvid seed dispersal. Issue 3 (5th December 2017) - Pesendorfer, Mario B.; Baker, Christopher M.; Stringer, Martin; McDonald‐Madden, Eve; Bode, Michael; McEachern, A. Kathryn; Morrison, Scott A.; Sillett, T. Scott
Abstract: Seed dispersal by birds is central to the passive restoration of many tree communities. Reintroduction of extinct seed dispersers can therefore restore degraded forests and woodlands. To test this, we constructed a spatially explicit simulation model, parameterized with field data, to consider the effect of different seed dispersal scenarios on the extent of oak populations. We applied the model to two islands in California's Channel Islands National Park (USA), one of which has lost a key seed disperser. We used an ensemble modelling approach to simulate island scrub oak ( Quercus pacifica ) demography. The model was developed and trained to recreate known population changes over a 20‐year period on 250‐km 2 Santa Cruz Island, and incorporated acorn dispersal by island scrub‐jays ( Aphelocoma insularis ), deer mice ( Peromyscus maniculatus ) and gravity, as well as seed predation. We applied the trained model to 215‐km 2 Santa Rosa Island to examine how reintroducing island scrub‐jays would affect the rate and pattern of oak population expansion. Oak habitat on Santa Rosa Island has been greatly reduced from its historical extent due to past grazing by introduced ungulates, the last of which were removed by 2011. Our simulation model predicts that a seed dispersal scenario including island scrub‐jays would increase the extent of the island scrub oak population on Santa Rosa Island by 281% over 100 years, and by 544% over 200 years. Scenarios without jays would result in little expansion. Simulated long‐distance seed dispersal by jays also facilitates establishment of discontinuous patches of oaks, and increases their elevational distribution. Synthesis and applications . Scenario planning provides powerful decision support for conservation managers. We used ensemble modelling of plant demographic and seed dispersal processes to investigate whether the reintroduction of seed dispersers could provide cost‐effective means of achieving broader ecosystem restoration goals on California's second‐largest island. The simulation model, extensively parameterized with field data, suggests that re‐establishing the mutualism with seed‐hoarding jays would accelerate the expansion of island scrub oak, which could benefit myriad species of conservation concern. Abstract : Scenario planning provides powerful decision support for conservation managers. We used ensemble modelling of plant demographic and seed dispersal processes to investigate whether the reintroduction of seed dispersers could provide cost‐effective means of achieving broader ecosystem restoration goals on California's second‐largest island. The simulation model, extensively parameterized with field data, suggests that re‐establishing the mutualism with seed‐hoarding jays would accelerate the expansion of island scrub oak, which could benefit myriad species of conservation concern.